STUDY OF PROCESS PARAMETERS AFFECTING 2D VIBRATION ASSISTED GASBAG POLISHING TECHNIQUE (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Polishing processes are mainly concerned with surface finish. This study is concerned with the effect of various parameters on surface finish in vibration assisted gasbag polishing process.In the present work, vibration mechanism is designed to study and analyze effect of various parameters such as vibration frequency (10-20 Hz), pressure inside the gasbag (0.5-1.5bar), Wt. of SiC (10-30gm) and Wt. of iron (15-25gm); in what sense they affect the surface roughness and machining depth. The silicon carbide of 15Î¼m size and iron powder are used as abrasives. The experiments are carried out on 45Ã—45 mm workpiece of thickness 5 mm of the die steel materials. Surface finish achieved by using soft gasbag tool and abrasive powder.Taguchi orthogonal array L27 method is used to carry out the experiments. Statistical methods are used to establish the relationships between responses and the process parameters and Grey relation is used for optimization of parameters.